Developing the Organic Agriculture Sub-Sector in Samoa - World Bank (Washington, DC, 2013)
The World Bank has provided technical assistance (TA) support to the Government of Samoa to help identify measures to strengthen agriculture sector institutions, to improve the performance of selected commodities - including livestock, fruits and vegetables and organic products - and to identify strategic agriculture infrastructure investments. This report provides information and analysis on opportunities for further development of organic products. The report also contains recommendations for activities that could be potentially supported as part of the proposed Samoa Agriculture Competiveness Enhancement Project (SACEP). This TA has identified a number of interventions to support further development of Samoan organic products. These include promoting domestic-oriented organic production targeted at the hospitality industry; support for up-grading and expanding existing value chains for export-oriented products including Misiluki bananas, coconut oil and products made from coconut oil; and investments in improved technology, better facilities, trial processing, and trial shipments to new destinations.